NARASI LIRIS FOTOGRAFI JURNALISTIK PADA MASA PANDEMI COVID-19: STUDI KASUS PROYEK FOTOGRAFI “STILL LIVES” OLEH THE NEW YORK TIMES - Aji Susanto Anom Purnomo; Novan Jemmi Andrea; Monica Revias Purwa Kusuma (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2021)
2020 is the year when the world is faced with a health crisis, namely the Covid-19 pandemic or also known as the Corona Virus. All aspects of life are affected by this crisis, the joints of humanity are faced with limitations. The mass media are intensively reporting various incidents regarding the Covid-19 pandemic. The stories are often accompanied by journalistic photos. One of the functions of photojournalism is to strengthen the story of what the media wants to convey. Journalistic photos during this pandemic usually feature scenes from medical activities, government policies and large narratives that are cold on empathetic human relations. However, different from most photojournalism in most mass media, The New York Times publishes